The effect of holes and free edges on the stress in laminated plates - Kaprielian, P.V. (1985)
This work is concerned with the study of the mechanical behaviour of elastic laminated plates subjected to different boundary conditions. For the most part, each lamina is taken to be a fibre-reinforced material which contains a family of straight, continuously distributed fibres.